Pengembangan Sistem Aplikasi Multimedia Interaktif Pada Pelajaran (Fisika Energy) Untuk Tingkat Sekolah Menengah Atas - Anas, Lukman (JTP - Jurnal Teknologi Pendidikan, 2019)
Characteristics of learning materials physics is sometimes very difficult to understand, requires the ability to control and manage the change between the different representations simultaneously. Representation is most often used by teachers are mathematical representations that other representations are often overlooked. On learning of physics required a thorough understanding of the concept that students can solve a problem in physics with good.Then to improve the quality of student learning, researchers will create a physics-based learning development is complex interactive multimedia on the subject of physics. Multimedia development that will be developed to have six stages, namely, concept, design, content collecting material, assembly, testing and distribution, to eventually used in the development of interactive media more particularly on the subject of physics. By results of data analysis showed an increase in the first cycle of 7.69% and the second cycle of 9.12%. Increased student learning outcomes is because during the learning process, teachers use interactive multimedia learning.